An Examination of Ethnic Hierarchies and Returns to Human Capital in the UK - Zwysen, Wouter (Social Inclusion, 2018)
This article focuses on the returns to human capital of migrants and minorities in the UK. The question of whether skills and qualifications are properly utilized is very pertinent given the global competition for skilled migrants and the aim of European and British markets to attract such workers. Using data from Understanding Society (2009 to 2017) we find that there is a clear evidence of ethnic hierarchies with black Caribbean and black African minorities generally most disadvantaged, while other white UK-born have the best outcomes compared to the white British. Western migrants generally do very well, but new EU migrants have high levels of employment, and low returns to their qualifications and relatively high levels of over-qualification. Foreign qualifications are generally discounted, and more so for migrants with less certain legal status or low language skills. Public sector employment plays an important role and is associated with the higher economic placement of migrants and minorities in the UK. There are some worrying trends however. Highly skilled migrants, particularly black migrants as well as those from Eastern Europe, come in with high qualifications, but their jobs do not match their skill levels.